Preparation and characterization of low-cost refractories for aluminum-melting-furnace linings from ferrotitanium slag. Issue 19 (1st October 2022) - Li, Yichong; Zhang, Han; Zhao, Huizhong; Yu, Jun; Ma, Jiuhong; Feng, Li; Liu, Yanli
Abstract: Management and utilization of solid waste are necessary for sustainable development in the metallurgical industry. This study focuses on the use of ferrotitanium slag (FTS) as a low-cost source of hibonite in the refractory lining of an aluminum-melting furnace. FTS enhances the resistance of castable samples to cryolite melt penetration but reduces their bulk density and cold mechanical strength. To explain this enhancement mechanism, we present a model in which the Al2 O3 and SiO2 components in the castable samples react with the cryolite melt to form a high-viscosity barrier layer against the molten cryolite. Moreover, the well-developed calcium hexaaluminate crystals in FTS, which show excellent resistance against Na + and F −, prevent the penetration of cryolite melt through the FTS aggregate area, and reduce the penetration speed. By promoting high-efficiency resource utilization, this study contributes to the development of a circular economy in the metallurgical industry.